Discovery of Anti-PD-L1 Human Domain Antibodies for Cancer Immunotherapy - Liu, Hao; Liu, Yanli; Zhao, Zhen; Li, Yuanke; Mustafa, Bahaa; Chen, Zhijin; Barve, Ashutosh; Jain, Akshay; Yao, Xiaolan; Li, Guangfu; Cheng, Kun (Frontiers in Immunology, 2022)
Immunotherapy using monoclonal antibodies targeting the PD-1/PD-L1 interaction has shown enormous success for various cancers. Despite their encouraging results in clinics, antibody-based checkpoint inhibitors have several limitations, such as poor tumor penetration. To address these limitations of monoclonal antibodies, there is a growing interest in developing low-molecular-weight checkpoint inhibitors, such as antibody fragments. Several antibody fragments targeting PD-1/PD-L1 were recently discovered using phage libraries from camel or alpaca. However, animal-derived antibody fragments may elicit unwanted immune responses, which limit their therapeutic applications. For the first time, we used a human domain antibody phage library and discovered anti-human PD-L1 human single-domain antibodies (dAbs) that block the PD-1/PD-L1 interaction. Among them, the CLV3 dAb shows the highest affinity to PD-L1. The CLV3 dAb also exhibits the highest blocking efficacy of the PD-1/PD-L1 interaction. Moreover, the CLV3 dAb significantly inhibits tumor growth in mice implanted with CT26 colon carcinoma cells. These results suggest that CLV3 dAb can be potentially used as an anti-PD-L1 inhibitor for cancer immunotherapy.